Education Quality Management through the Indirect Assessment of Expected Learning Outcomes in the Undergraduate Training Program of Business Administration - Ai Cam, Tran (VNU Journal of Science: Policy and Management Studies; Vol 39 No 2DO - 10.25073/2588-1116/vnupam.4418, 2023)
Assessing graduates' achievements of expected learning outcomes (ELOs) is an issue that must be addressed today to guarantee that the program is designed and implemented in an adequate way that meets the social requirements. This research sets a theoretical framework for an indirect assessment of ELOs regarding all knowledge, skills, personal autonomy, and relative responsibility. The evaluation is implemented through surveys and questionnaires for the Undergraduate Training Program of Business Administration at Nguyen Tat Thanh University. The findings are compared to the results of the direct measurements and offer recommendations for improving and enhancing the program's quality.